Assessment of Students' Perception and Satisfaction with Hostel Accommodation in Afe Babalola University, Ado Ekiti, Nigeria - Tijani, Nasiru O.; Habeeb, Mohammed A.; Umeh, Somtochukwu Nwogo (Àgídìgbo: ABUAD Journal of the Humanities, 2015)
The study examined Students' Perception and Satisfaction with Accommodation Facilities in Afe Babalola University Ado- Ekiti. Information used for the study was collected with the aid of questionnaire administration. Multi-stage random sampling technique was adopted for the study. Firstly, the researchers divided the study population into two based on gender, that is, male and female. Secondly systematic random sampling technique was used to select every forth rooms in all the hostels for data collection at the end 75female and 75 male respondents were selected, constituting about 3% of the total study population. Findings revealed that student were generally satisfied with the facilities provided in their hostels but complained that the facilities are poorly maintained due to inadequate water supply to hostels. The study concluded thatABUAD management should ensure adequate supply of water to all hostels as a way forward and constantly maintain hostel equipment/facilities whenever need arises. The study is significant to the management of Afe Babalola University and those that are saddled with the responsibility of maintaining hostel accommodation facilities in their campus.